The Cost of Inner Critique on Well-Being: A Mediational Model of Perfectionism - Surjan, Paras (Thapar Institute of Engineering and Technology, 2025)
The present study focuses on how self-critical rumination affects our psychological well-being and how perfectionism works as a mediator between them. self-critical rumination and psychological wellbeing are negatively correlated and perfectionism and psychological well-being are negatively associated. There were (104) participants within the age range of 18 to 30. There were three scales used for this study. Self-Critical rumination Scale was developed by Smart et al., (2016) was used to measure self-critical rumination. Psychological Wellbeing (18 items) scale by Ryff (1995), A shorter version of the original scale of psychological wellbeing scale, was used. It has five sub scale. BTPS-SF Feher et al., (2019), a short form of the original scale of the big three perfectionism scale was used to evaluate perfectionism. It has three sub scale. Results of this study showed a significant partial mediation that self-critical rumination affects psychological wellbeing and perfectionism working as a mediator between self-critical rumination and psychological wellbeing.
Keywords: Self-Critical Rumination; Psychological well-being; Perfectionism; Self-Evaluation; Superiority